Critical Barriers in Reverse Logistics Implementation: Case Study on Construction Machinery Remanufacturing Company in Indonesia - Evi Yuliawati; Hastawati Chrisna Suroso (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2021)
Increasing customer awareness of environmental issues, including awareness of the decreasing capacity of landfills for final disposal, requires industries puts more thought into the reverse logistics (RL) process. Implementing this process requires an in-depth study, especially on barriers to implementing an effective RL system. Based on these problems, this study aims to analyze the RL system's barriers, especially in Indonesian construction machinery remanufacturing companies. In general, the barriers to implementing an effective RL system are categorized as internal and external barriers. Data gathering was carried out to identify internal and external barriers to implementing an effective RL system in construction machinery remanufacturing companies. This step was carried out through literature studies, interviews with academics and practitioners in the field of RL systems, and distributing questionnaires. Furthermore, the Analytical Hierarchy Process (AHP) approach ranks the barriers to implementing the RL system, which is a priority for construction machinery remanufacturing companies. This research contributes to a compilation of RL system barriers, especially in the construction machinery remanufacturing industry. The result analysis using AHP showed that the priority score of criteria activity front-end is the biggest.